Vehicle tracking and speed estimation system - Chan, Chia Yik (2012)
This project is intends to develop a vehicle tracking and speed estimation using digital image processing technique. Therefore this project needs a video input to make the system work.The system is designed to track the vehicle position and calculate its moving speed.The method that uses to estimate the speed of the moving vehicle currently is RADAR (Radio Detection and Ranging)But this method requires high end equipment,which means the cost for this method is high.Therefore an alternative way is needed.This proposed method is using the image processing technique.This system consists of 4 major steps:1)image acquisition 2)image background subtraction 3)location detection 4)speed estimation.The rate of accuracy for this system is expected to have 99%.